2016
DOI: 10.1063/1.4948446
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of In-rich InGaN and InN/InGaN superlattices

Abstract: The thermoelectric properties of n-type InGaN alloys with high In-content and InN/InGaN thin film superlattices (SL) grown by molecular beam epitaxy are investigated. Room-temperature measurements of the thermoelectric properties reveal that an increasing Ga-content in ternary InGaN alloys (0 < x(Ga) < 0.2) yields a more than 10-fold reduction in thermal conductivity (κ) without deteriorating electrical conductivity (σ), while the Seebeck coefficient (S) increases slightly due to a widening band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 44 publications
(60 reference statements)
2
8
0
Order By: Relevance
“…III-nitride semiconductors, especially GaN and InN, are promising materials in a wide range of emerging applications, such as power electronics 2 and light-emitting diodes (LEDs) 1 . Efficient thermal management of these high-power-density devices requires detailed understanding of phonon scattering by dislocations, commonly found in III-nitrides due to limitations of current growth techniques 25 . Also, we present a new route to anisotropically direct heat flow via dislocations, which could be used to guide and spread heat in electronic devices 17 .…”
mentioning
confidence: 99%
“…III-nitride semiconductors, especially GaN and InN, are promising materials in a wide range of emerging applications, such as power electronics 2 and light-emitting diodes (LEDs) 1 . Efficient thermal management of these high-power-density devices requires detailed understanding of phonon scattering by dislocations, commonly found in III-nitrides due to limitations of current growth techniques 25 . Also, we present a new route to anisotropically direct heat flow via dislocations, which could be used to guide and spread heat in electronic devices 17 .…”
mentioning
confidence: 99%
“…Extrinsic phonon scattering centers, such as atomic intermixing, interface roughness and contamination, would easily scatter phonons and bury the phonon's intrinsic elastic and inelastic transport processes across interfaces 22 . Epitaxial metal/semiconductor interfaces are usually used to study the intrinsic interface phonon transport due to their importance and high quality 6,[22][23][24] . However, previous studies on epitaxial interfaces used typically lacked atomic-level structural details 12,21 with interface roughness and atomic intermixing often ignored, thus only lead to qualitative analysis and limit our understanding of intrinsic phonon transport across interfaces.…”
Section: With Increasing Interface Roughness Inelastic Phonon Transport Rapidly Diminishes Our Results Provide New Insights On Phonon Tramentioning
confidence: 99%
“…For nanoscale and microscale GaN devices, interfaces play a critical rule in impeding heat dissipation. The thermal boundary resistance (TBR) at interface is equivalent to as large as micrometer-thick heat sink's thermal resistance, and cannot be ignored [18][19][20][21][22]. For example, Ziade et al [23] reported that the thermal boundary conductance (TBC, which is the reciprocal of TBR) at the interface of GaN/SiC was 230 MW•m −2 •K −1 , which is equivalent to the thermal resistance of 1.7-μm-thick SiC.…”
Section: Introductionmentioning
confidence: 99%